2020
DOI: 10.1186/s12888-020-02960-y
|View full text |Cite
|
Sign up to set email alerts
|

The potential impact of an anti-stigma intervention on mental health help-seeking attitudes among university students

Abstract: Background The reluctance of young adults to seek mental health treatment has been attributed to poor mental health literacy, stigma, preference for self-reliance and concerns about confidentiality. The purpose of this study was to examine the potential impact of an anti-stigma intervention that includes education about depression, information about help-seeking as well as contact with a person with lived experience, on help seeking attitudes. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 54 publications
2
26
0
Order By: Relevance
“…Participants of this study had to complete 3 sets of identical questionnaires; prior to commencement of the intervention (baseline), immediately after the intervention (time-point 2), and 3-months from date of intervention (time-point 3). More details of the ARTEMIS study design can be found in previously published articles ( 18 , 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…Participants of this study had to complete 3 sets of identical questionnaires; prior to commencement of the intervention (baseline), immediately after the intervention (time-point 2), and 3-months from date of intervention (time-point 3). More details of the ARTEMIS study design can be found in previously published articles ( 18 , 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…Potential strategies addressing stigma-related barriers include facilitating population based-literacy programs to transit positive mental health messaging to the wider university cohort and incorporating social content into mental health awareness training to improve mental health knowledge and decrease stigmatising attitudes (Stuart, 2016). By incorporating reducing stigma strategies, both antistigma and help-seeking behaviours have been shown to increase (Shahwan et al, 2020). Strategies that include promoting services using student testimonials and terminology, and providing information aimed at dispelling negative perceptions and re-framing services in terms less associated with mental illness, such as consultations, coaching or seminars, may also be helpful in reducing the perceived stigma associated with accessing support services (Sanagavarapu & Abraham, 2020).…”
Section: Top 3 Strategies To Relieve/reduce Stress Recommended Tomentioning
confidence: 99%
“…A pilot study on an anti-stigma course toward mental disorders, which consisted of three components, namely, social contact, role-playing, and critical reflection strategies, showed that participants' stigma attitudes were significantly reduced after the 18-week anti-stigma course ( 39 ). Another study examining the potential impact of an anti-stigma intervention on help-seeking attitudes, which included education about depression, information about help-seeking, and contact with a person with lived experience, showed improvements in help-seeking attitudes ( 40 ). Our data indicate that providing accurate COVID-19-related information through social media and newspapers/TV may be effective as these are the main sources they used to get COVID-19-related information.…”
Section: Discussionmentioning
confidence: 99%